Analisis Regresi Logistik Ordinal pada Pengaruh Pelayanan Terhadap Kepuasan Pasien Rawat Inap di Rumah Sakit Murni Teguh Medan - Simangungsong, Monalisa; Pane, Rahmawati; Manurung, Asima; Tarigan, Enita Dewi br. (Jurusan Matematika FMIPA UNM, 2024)
Abstract. Hospitals play an important role in supporting public healt by providing high quality services, especially in providing optimal services for inpatients. Patient satisfaction is the main indicators to assess the quality of services in the hospital. This research aims to determine the effect of services on the level of satisfaction of inpatients at Murni Teguh Hospital using the ordinal logistic regression method. The results showed 44% of respondents were satisfied and 29% of respondents were very satisfied. Variables that have a significant effect on patient satisfaction are food service, medical facilities and medicines, and administrative services. The Negelkerke’s coefficient of determination of 0.825 indicates that 82.5% of the predictor variables affect the overall assessment of impatient satisfaction. The results of the model interpretation show that the highest chance of patients to feel very satisfied is in the medical facilities and medicines variable with an odds ratio of 2.959.